2009
DOI: 10.1086/599118
|View full text |Cite
|
Sign up to set email alerts
|

Patients' Beliefs and Perceptions of Their Participation to Increase Healthcare Worker Compliance with Hand Hygiene

Abstract: This study identifies several sociodemographic characteristics associated with the intention to ask nurses and physicians about hand hygiene and underscores the importance of a direct invitation from healthcare workers to increase patient participation and foster patient empowerment. These findings could guide the development of future hand hygiene-promotion strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
78
2
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 31 publications
6
78
2
2
Order By: Relevance
“…However, patients fear questioning their doctors. Similar patient empowerment programs have shown success in increasing HH compliance, 5,9 which suggests that patient empowerment could be harnessed on an increased scale to improve compliance of HCWs. 10 Our program has demonstrated that future research should specifically address the patient-doctor relationship and ways to facilitate open communication.…”
mentioning
confidence: 99%
“…However, patients fear questioning their doctors. Similar patient empowerment programs have shown success in increasing HH compliance, 5,9 which suggests that patient empowerment could be harnessed on an increased scale to improve compliance of HCWs. 10 Our program has demonstrated that future research should specifically address the patient-doctor relationship and ways to facilitate open communication.…”
mentioning
confidence: 99%
“…15,22,23 The findings in the current study are particularly important as the views were taken after a detailed presentation of the risks of hospital acquired infections and the critical role of hand hygiene in addressing this avoidable harm. Reasons for not asking spanned from fear of repercussions for future care, respect of professional knowledge and competence, to empathy for a busy, over-stretched workforce.…”
Section: Discussionmentioning
confidence: 98%
“…Our results are aligned with previous international studies that have reported hospital patient willingness (ie, to remind them to perform HH) levels ranging from 24%-79%. [16][17][18][19][20][21] The willingness of our patients to participate varied considerably depending on the activity that they were presented with. Patients reported that they were highly willing to ask general questions about the signs and symptoms of infection but less likely to engage with staff and challenge them about their HH behaviors.…”
Section: Discussionmentioning
confidence: 99%